Investigative competences: A cross-cutting analysis in higher education teachers (2020)
The investigative competences of the teachers of the Architecture program of the Francisco de Paula Santander University are established under a comparative scheme between the years 2017-2020. A quantitative methodology was used, under a measurement dimension, under non-experimental, crosssectional, descriptive and comparative research. The importance of the development of investigative competences in Higher Education was established and the progress of the teachers in the program with respect to investigative competencies was highlighted, highlighting the dimension of Knowledge dissemination.